Behavioral interventions in informal seed systems to nudge sustainable demand for quality seed of sweetpotato - Okello, J.J.; Just, D.R.; Verschoor, A.; Mulwa, C.K.; Ojwang, S.O.; Namanda, S.; Yada, B.; Ssali, R.T.; Okim, M.B.; Mutiso, J.M.; Rajendran, S.; Campos, Hugo (Elsevier, 2025)
CONTEXT: The introduction of quality-certified seed (QCS) in the informal farmer network-based seed systems, which have largely relied on informal signals of quality, represents a promising innovation towards integrated seed sector development, combining formal and informal sector elements. At the same time, behavioral nudges have emerged as potentially powerful ways to encourage the uptake of innovations among smallholder farmers in developing countries.